PATH-26. NEURO-ONCOLOGY NEXT-GENERATION SEQUENCING 219-GENE PANEL FOR COMPREHENSIVE CLINICAL TESTING. (5th November 2018) - Ida, Cristiane; Barr Fritcher, Emily; Zysk, Christopher; Voss, Jesse; Wu, Xianglin; Balan, Jagadheshwar; Kollmeyer, Thomas; Raghunathan, Aditya; Giannini, Caterina; Klee, Eric; Kipp, Benjamin; Jenkins, Robert
Abstract: Molecular parameters were incorporated in the WHO classification of central nervous system (CNS) tumors. Despite advances in understanding the molecular biology of CNS tumors, targetable genomic abnormalities are lacking. To identify diagnostically, prognostically and potential therapeutically relevant abnormalities, we developed a next generation sequencing (NGS) assay for formalin-fixed paraffin-embedded (FFPE) tissue that evaluates 219 genes associated with adult and pediatric CNS tumors. This test consists of a DNA and an RNA subpanel for the detection of sequence alterations and gene rearrangements (known gene fusions and abnormal transcript variants, and novel fusion transcripts that contain any of the interrogated genes as a partner). The assay utilizes an amplicon-based approach with molecular barcode chemistry (to allow traceability of PCR artifacts/duplicates), Illumina sequencing and custom bioinformatics pipelines. Analytical validation included 175 samples. Overall concordance with alternative methods were 99% and 96% and success rates were 97% and 95% for the DNA and RNA subpanels, respectively. Inter and intra-assay reproducibility was 100% for both subpanels. The limit of detection (analytical sensitivity) for nucleic acid input and tumor content were 8.5 ng and 30%, and 10 ng and 10% for the DNA and RNA subpanels, respectively. The analytical specificity was high, with per base DNA sequencing false positive rate <0.4% and absent fusion transcript detection in non-neoplastic samples. We developed a robust 219-gene neuro-oncology NGS assay suitable for clinical testing of FFPE specimens, including small biopsies with low tumor content. This test, combined with chromosomal microarray analysis, detects nearly all single nucleotide variants, fusion rearrangements and copy number changes associated with CNS tumors. These tests are intended to assist in the diagnosis, prognosis and therapeutic management of adult and pediatric patients with CNS tumors, and have the potential to unravel novel genomic abnormalities and expand the understanding of the molecular biology of such tumors.